Coccygeal polypoid eccrine nevus associated with imperforate anus and unilateral multicystic kidney dysplasia. (8th May 2016) - Frouin, Eric; Riviere, Benjamin; Maillet, Olivier; Willems, Marjolaine; Kalfa, Nicolas; Costes, Valerie; Bessis, Didier
Abstract : Eccrine nevi are rare hamartomas characterized by an increase in the number or size of eccrine glands. A polypoid form located in the coccygeal area has been described in a few cases and termed coccygeal polypoid eccrine nevus (CPEN). No association with internal malformations was reported in any of these cases. We describe herein a case of CPEN associated with imperforate anus and unilateral multicystic kidney dysplasia. We review the clinical and pathological characteristics of CPENs and discuss the differential diagnoses.